A multi-body model for comparative study of cervical traction simulation – comparison between inclined and sitting traction. Issue 8 (11th June 2019) - Wong, Lawrence K. F.; Luo, Zhiwei; Kurusu, Nobuyuki; Fujino, Keiji
Abstract: A computer simulation model was developed to compare the result of cervical traction therapy in inclined and sitting traction positions. The behavior of the model was shown to match with the intervertebral changes in the upper and lower spine from the data of a radiographic experiment. Both the results of the experiment and the simulation also showed that in the inclined position, the amount of posterior separations in the upper cervical spine remains constant regardless of traction angle, while the posterior separations at lower cervical spine increases along with traction angles. Using the simulation model, parametric studies were conducted to investigate the intervertebral space changes in response to different traction angles in the inclined and sitting positions. When using the sitting position, the subject's hip joint stiffness was shown to cause larger variations in the intervertebral space than in the inclined position. In addition, variations in the tension/compression stiffness was shown to cause the largest changes in the resulting separations in both positions but the variations in anterior space changes were larger in the sitting position. Our study suggests that the inclined position is less sensitive to variations in the subject's body parameters and is able to provide a more reliable and predictable traction result than the sitting position.